Production of renewable hydrocarbon fuel via titanium oxide-alumina (TiO2-Al2O3) catalytic deoxygenation reaction / Ooi Xian Yih - Ooi, Xian Yih (2020)
The renewable hydrocarbon-like biofuel from biomass is crucial to substitute fossil fuel. Catalytic deoxygenation is a biofuel upgrading process to eliminate the high oxygen content in biofuel which will lead to corrosion, instability and lower heating value problems. The choice of support is significant to provide the maximum acid strength for the hydrogenolysis of C-O bonds. Al2O3 supported catalyst has drawn attention due to the high acidity. However, the high acidity leads to coke deposition, unstable and deactivation of the catalyst. Thus, it is important to develop methods to improve catalyst performance, reduce catalyst coking and enhance catalyst lifetime. Recently, Al2O3-TiO2 mixed oxide catalyst has drawn increasing attention in deoxygenation process owing to its unique properties which can solve the issues from Al2O3. Controlled synthesis method is significant to improve the effectiveness of Al2O3-TiO2 in catalytic reaction since the physicochemical properties of the catalyst are co-related to the processing methodology. A series of mesoporous Al2O3-TiO2 mixed oxide catalysts with different TiO2 content (0.1Ti-0.9Al, 0.2Ti-0.8Al and 0.3Ti-0.7Al) have been synthesized. The physicochemical properties of the catalysts were characterized by XRD, FESEM-EDX, BET, FTIR, FTIR-Py, NH3-TPD and TGA. The deoxygenation (DO) of triglyceride (i.e. triolein) was carried out in the absence of hydrogen and solvent. The mesoporous Al2O3-TiO2 catalysts showed high performance on the catalytic activity. It was found that 0.2Ti-0.8Al catalyst exhibited the highest conversion (76.86%), and selectivity (27.26%) toward n-C15 + n-C17 at 380 °C for 4 h. The excellence performance of mesoporous Al2O3-TiO2 was attributed to its acidity, mesoporosity and large surface area. The results reveal that the mesoporous Al2O3-TiO2 catalyst is a promising catalyst for the synthesis of hydrocarbon-like biofuel via deoxygenation.